Modal Sosial Industri Keripik Sanjai di Kota Bukitinggi - Verthasari, Indah; Hidir, Achmad (Indonesian Journal of Education and Development Research, 2025)
The Sanjai area, which is one of the sanjai chip industries in Bukittinggi City, is still actively engaged in the sanjai chip industry. The sanjai chip industry will be able to survive when they can apply forms of social capital in their business groups. The purpose and objective of this research is to find out the elements of social capital contained in the business activities of the sanjai chip industry in Bukittinggi city using a descriptive qualitative approach method and the selection of information carried out by purposive sampling technique, namely obtaining data from informants based on certain criteria or limitations. The criteria or limitations are the sanjai chips industry that has been running for more than 20 years, and already has its own sanjai shop. The data collection techniques used in this research are observation, interview and documentation techniques. The conclusion of the results of this study is that the elements of social capital contained in the sanjai chip industry consist of three, namely social networks, norms, and trust, where these three theories need each other and bind each other in each related individual, with the elements of social capital that are intertwined in the sanjai chip industry business will provide comfort to each sanjai chip industry and be able to maintain the existence of this sanjai chip industry business until now.